SINTESIS HIBRIDA 2,7-DISULFONATO-NAFTALENA-5-HIDROKSI-4- AMINO-N-PROPIL SILIKA DAN SIFAT ADSORPSINYA TERHADAP ION Mg, Ca, Cu(II), Cd(II) - , CHOIRIL AZMIYAWATI; , Prof. Dr. rer.nat. Nuryono, M.S ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Application of silica gel (SG) for metal ion adsorption is less effective due to limitation of it a silanol and siloxane active sites. The silanol groups can be modified with sulfonate groups to improve their effectiveness, especially in adsorb hard metal ions. The aims of this research are synthesis of 2,7- disulfonatonaphthalene-5-hydroxy-4-amino-N-propyl silica (HDSS) by using rice hull ash as silica source and its application for adsorption of Mg, Ca, Cu(II) and Cd(II) ions in aqueous solution. The first steps of the study was attachment of disulfonato groups of 4- amino-5-hydroxy-2,7-naphthalenedisulfonate monosodium salt (AHNSNa) to 3- chloropropyltrimethoxysilane (CPTS), to produce N-propiltrimetoksisilan-4- amino-5-hidroksi-2,7-disulfonatonaftalena (PTMDS) with and without reflux (PTMDSr and PTMDSnr, respectively). Synthesis of HDSS was carried out through sol-gel process and grafting. The sol-gel process was conducted by reacting of PTMDSr and PTMDSnr with sodium silicate solution at pH of 7.0 to find HDSSR and HDSSNR, respectively. For grafting technique, commercial silica gel was refluxed with PTMDSnr in sodium carbonate 0.5M to result in HDSSG. The products of HDSS were characterized with XRD, 29 Si-NMR, GSA, FTIR spectrophotometry and SEM/EDX. Thermodynamics and kinetics properties were evaluated based on adsorption data of investigated metal ions in a batch system at various concentrations and times, respectively. Product HDSS was proved by appearing of the chemical shift 29 Si-NMR spectra supported by infrared spectra indicating the presence of sulfonate groups, aromatics, ethylene and CN bond. HDSS obtained through sol-gel (HDSSR and HDSSNR) and grafting (HDSSG) process had a surface area and mean pore radius greater than SG. More over HDSSNR surface area (417.597 m 2 /g) was greater than HDSSG (51.323 m 2 /g) with a mean pore radius of 44.01 and 154.1 Ã, respectively. Adsorption rate constant (k) and adsorption capacity of HDSS for Mg, Ca, Cu(II), and Cd(II) ions were greater than that of SG at pH 6.0. The capacity and rate constant (k) of desorption for Mg and Ca ions from HDSS is higher than that on SG, in both individual and biner system. Generally, hybridization of sulfonate groups on SG increases the ability of adsorption and desorption rate of the metal ions investigated.